2017
DOI: 10.1021/acs.jafc.7b00929
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rotundone as a Potent Odor-Active Compound of Several Kinds of Fruits

Abstract: An investigation of the aromas of grapefruit, orange, apple, and mango revealed the presence of an odor-active compound that gave off a strong woody odor when assessed by gas chromatography-olfactometry. We isolated the compound from a high-boiling fraction of an orange essential oil, and subsequent nuclear magnetic resonance analyses of the isolated compound identified it as rotundone. Mass spectra and retention indices obtained from aroma concentrates of grapefruit, apple, and mango were identical to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…13 C NMR: δ 210.7, 207.8, 175.1, 145.5, 51.4, 42.9, 37.9, 32.0, 31.9, 28.3, 27.3, 26.9, 19.1, 17.5. GC-MS (EI): 221 (10), 220 (M + , 66), 205 (6), 191 (10), 178 (19), 177 (100), 175 (13), 163 (19), 162 (9), 161 (6), 159 (16), 150 (9), 149 (18), 147 (21), 145 (10), 136 (8), 135 (50), 134 (6), 133 (16), 131 (7), 121 (14), 119 (15), 117 (7), 108 (6), 107 (30), 105 (23), 93 (28), 92 (6), 91 (37), 81 (9), 79 (21), 78 (6), 77 (22) 71 (6), 69 (10), 67 (7), 65 (10), 55 (12), 53 (8), 43(50), 41 (14), 39 (9). HRMS (EI) calculated for C 14 H 20 O 2 : 220.14644, found 220.14694.…”
Section: ■ Materials and Methodsunclassified
See 1 more Smart Citation
“…13 C NMR: δ 210.7, 207.8, 175.1, 145.5, 51.4, 42.9, 37.9, 32.0, 31.9, 28.3, 27.3, 26.9, 19.1, 17.5. GC-MS (EI): 221 (10), 220 (M + , 66), 205 (6), 191 (10), 178 (19), 177 (100), 175 (13), 163 (19), 162 (9), 161 (6), 159 (16), 150 (9), 149 (18), 147 (21), 145 (10), 136 (8), 135 (50), 134 (6), 133 (16), 131 (7), 121 (14), 119 (15), 117 (7), 108 (6), 107 (30), 105 (23), 93 (28), 92 (6), 91 (37), 81 (9), 79 (21), 78 (6), 77 (22) 71 (6), 69 (10), 67 (7), 65 (10), 55 (12), 53 (8), 43(50), 41 (14), 39 (9). HRMS (EI) calculated for C 14 H 20 O 2 : 220.14644, found 220.14694.…”
Section: ■ Materials and Methodsunclassified
“…5,6 Furthermore, in our previous study, we also found rotundone, which has a woody odor, as an another potent odorant in white grapefruit peel by GC-O for the first time. 9 Rotundone is a sesquiterpenoid, which was first isolated from essential oils of nut grass weed (Cyperus rotundus) 50 years ago; 10 however, it has been clarified recently that rotundone is an odorant responsible for peppery, spicy, and woody odors, and its identification as an odor-active compound in patchouli oil, 11 Shiraz wine, 12 Shiraz grape, 12 spices, 12 oak-aged spirits, 13 frankincense (Boswellia sacra) oil, 14 and cypriol oil 15 was reported. Quantitation of rotundone in these natural products has been well studied, but there is still scope for research on the quantitation in grapefruit and its importance as a contributor to the odor of grapefruit; therefore, in this study, we evaluated and quantitated rotundone in white grapefruit peel (WGP), pink grapefruit peel (PGP), white grapefruit juice (WGJ), and pink grapefruit juice (PGJ) by AEDA and SIDA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At Hasegawa Co ., the olfactory profile of epi ‐rotundone ( 1b ) was recently explored, and (−)‐rotundone 1a has been identified in the volatile fraction of Boswellia sacra gum resin contributing to the aroma of frankincense 1 . (−)‐Rotundone has also been identified as potent odor‐active component in the aromas of grapefruit, orange, apple and mango [8] …”
Section: Introductionmentioning
confidence: 99%
“…1 (À )-Rotundone has also been identified as potent odor-active component in the aromas of grapefruit, orange, apple and mango. [8] (À )-Rotundone 1a has been prepared from guaiac wood oil (Scheme 1), from which the structurally related precursors (À )-α-guaiene (2) and (À )-guaiol (3) are obtained by a tedious and low-yielding extraction. [9 -11] The allylic oxidation of sesquiterpene 2 has been effected with iron(III) porphyrin catalysts, [12,13] through electrochemical oxidation, [14] through chromate oxidation or simply by aerial oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation